Analysis of Determinants of Consumer Demand for Shallots (Allium cepa L.) in Langsa City - Safrizal, Safrizal; Gustiana, Cut; Isma, M. Fauzan; Mahdi, Saiful; Hadisugelar, Danar (Universitas Serambi Mekkah, 2025)
Shallots (Allium cepa, L) are one of the main horticultural commodities consumed by the Indonesian people as a spice for cooking and traditional medicine. The demand for shallots has increased as the population has increased, but its availability in the market often fluctuates due to seasonal factors, pests, and production constraints that cause price volatility. This study aims to analyze the factors that affect the demand for shallots in Langsa City, focusing on three main variables: price, income, and consumer taste. The research method uses a quantitative approach with survey techniques and multiple linear regression analysis. The results of the study show that price has a negative influence on demand, consumer taste has a significant positive effect, while income has no effect on demand for shallots. This research provides insight for the government in setting policies to stabilize the price and supply of shallots in Indonesia.